2002
DOI: 10.1097/00024382-200210000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Hemodynamic Effects of Hypertonic Solutions: Sodium-Lactate Versus Sodium Chloride Infusion in Postoperative Patients

Abstract: Although hypertonic saline has been proposed as an intravenous resuscitation fluid, the beneficial effects of the sodium load are associated with potentially deleterious effects of chloride. Since the physiological lactate anion is well metabolized, hypertonic lactate solution could represent an interesting alternative. The aim of this study was to compare metabolic and hemodynamic effects of hypertonic infusion of sodium lactate versus sodium chloride in three groups of surgical patients who underwent electiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Clinically significant hyperkalemia can result following the infusion of a number of RBCs units, especially in infants and small children. Whether hyperlactatemia itself has an effect on cellular function remains unclear, but in vitro studies suggested that lactate has depressive effects on cardiovascular function, and can facilitate cardiac arrhythmias and other adverse effects [31, 32]. In order to study whether K and LA in the SSRBCs have toxic effects on hiPS-CMs, we prepared LA solution, K solution and a mixture of K and LA solution to evaluate their effects on hiPS-CMs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically significant hyperkalemia can result following the infusion of a number of RBCs units, especially in infants and small children. Whether hyperlactatemia itself has an effect on cellular function remains unclear, but in vitro studies suggested that lactate has depressive effects on cardiovascular function, and can facilitate cardiac arrhythmias and other adverse effects [31, 32]. In order to study whether K and LA in the SSRBCs have toxic effects on hiPS-CMs, we prepared LA solution, K solution and a mixture of K and LA solution to evaluate their effects on hiPS-CMs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…60 However, infusion of large amounts of sodium lactate, which increased blood lactate levels up to 15 mEq/L, did not depress cardiac output in patients following heart transplantation. 61 Further studies are necessary to examine the potential merits of lactate removal.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on infusion of lactate solutions to postoperative patients was shown to be safe. 55 Also, the fact that lactate generation in states of respiratory alkalosis, stress, or altered carbohydrate metabolism without sepsis is not associated with worse outcomes supports the fact that lactic acid alone may not be maladaptive.…”
Section: Impact Of La On Morbidity and Mortalitymentioning
confidence: 95%